Interaction between activities of daily living and cognitive function on risk of depression - Zhang, Fenghao; Yang, Wenyan (Frontiers in Public Health, 2024)
Objective: There is a lack of literature about the joint effects of activities of daily living (ADL) limitation and cognitive impairment on depression. This study aimed to estimate the association of ADL limitation and cognitive impairment with depression among Chinese older adults aged 65 and above and to test their interaction on both additive and multiplicative scales.Methods: Data was drawn from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), including 11025 eligible participants. Logistic regression models were fitted, and both multiplicative and additive interactions for ADL limitation and cognitive impairment were tested.Results: A total of 3019(27.4%) participants reported depressive symptoms. After controlling for potential confounding factors, ADL limitation and cognitive impairment were both positively associated with depression. The adjusted additive interaction of basic and instrumental activities of daily living limitation were 2.47 (95%CI:1.92-3.19) and 3.67 (95%CI:2.88-4.66), respectively, but the multiplicative interaction items were both insignificant.ADL limitation and cognitive impairment were both risk factors for depression among Chinese older adults. Moreover, the significant interaction of ADL limitation and cognitive impairment was found in the additive model, suggesting that improving ADL may be helpful in reducing the risk of depression among older people with cognitive impairment.